ETUDE DIACHRONIQUE DE LA REGRESSION DU COUVERT VEGETAL DE LA COMMUNE DE ZAAROURIA (WILAYA DE SOUK AHRAS) : APPROCHE PAR TELEDETECTION ET SIG - Asma,BOULEBDA; Asma,HARCHANI (My University, 2020)
The region of Zaarouria represents a very remarkable phytogeographical ensemble from the point of view of its forest vegetation. Anthropogenic action, climatic factors, fires and other forms of degradation are the main causes of the deterioration of this forest vegetation. The method adopted to study this regression is based on remote sensing and mapping techniques. This study aims to highlight the extent of changes in forest cover between 2007 and 2019 based on satellite images LANDSAT TM5 (2007) and LANDSAT 8 OLI (2019). These, made it possible to make a spatiotemporal analysis of the dynamics of regression of the forest vegetation, in the region of Zaarouria.. حعخبز منطقت انشعزوريت مجمىعت مميشة من حيج انخنىع اننباحي انجغزافي بإمخياس من وجهت اننباحاث انحزجيت. اإلجزاءاث انبشزيت انعىامم انمناخيت انحزائق واالشكال األخزي من انخذهىر هي األسباب انزئيسيت نخذه ور هذه انغابت اننباحاث وحسخنذ انطزيقت انمعخمذة نذراست هذا انخزاجع إنً حقنياث االسخشعار عن بعذ ورسم انخزائط حهذف هذه انذراست إنً حسهيط انضىء عهً مذي انخغيزاث في انغطاء انحزجي بين عامي 2007 و2019 باالسخناد إنً صىر األقمار انصناعيت .LANDSAT TM5 (2007) و LANDSAT 8 OLI (2019) قذ مكنج هذه انذراساث من إجزاء ححهيم نابع نمحطىراث انمخعهقت بانحذار اننباحاث انحزجيت في منطقت انشعزوريت..... The region of Zaarouria represents a very remarkable phytogeographical ensemble from the point of view of its forest vegetation. Anthropogenic action, climatic factors, fires and other forms of degradation are the main causes of the deterioration of this forest vegetation. The method adopted to study this regression is based on remote sensing and mapping techniques. This study aims to highlight the extent of changes in forest cover between 2007 and 2019 based on satellite images LANDSAT TM5 (2007) and LANDSAT 8 OLI (2019). These, made it possible to make a spatiotemporal analysis of the dynamics of regression of the forest vegetation, in the region of Zaarouria.